Using genetic algorithm to manage and schedule temperature sensor calibration - Thepmanee, Teerawat; Masuchun, Ruedee (My University, 2011)
Currently, generating a schedule to calibrate temperature sensors for both laboratory calibration and field calibration are very time-consuming and inefficient, especially when several temperature sensors await for being calibrated and the due dates are required to be specified in advance. General rule of thumb used is first-come-first-served but the due date is difficult to determine in advance. Moreover, overview of which standards will be required and, if required, at what temperatures each of them should be set to cannot be globally visualized. Another method is to calibrate those temperature sensors requiring same temperature together but the experience is strictly required to avoid overwhelming calculation time. This paper presents the application of scheduling technique using genetic algorithm to schedule temperature sensor calibration. The fitness function is to minimize the time required to calibrate all temperature sensors. Our method takes little time to generate good schedule while the due date of each temperature sensor can be at once stated and the global view of required standards can be anticipated for further preparation. Moreover, our method is easy to use and suitable for anyone without the experience in scheduling temperature sensors. © 2011 ISSN.
Keywords: Calibration management; Genetic algorithm; Mathematical model; Scheduling; Temperature sensor calibration